The genetic landscape of endometrial clear cell carcinomas. Issue 2 (5th September 2017) - DeLair, Deborah F; Burke, Kathleen A; Selenica, Pier; Lim, Raymond S; Scott, Sasinya N; Middha, Sumit; Mohanty, Abhinita S; Cheng, Donavan T; Berger, Michael F; Soslow, Robert A; Weigelt, Britta
Abstract: Clear cell carcinoma of the endometrium is a rare type of endometrial cancer that is generally associated with an aggressive clinical behaviour. Here, we sought to define the repertoire of somatic genetic alterations in endometrial clear cell carcinomas (ECCs), and whether ECCs could be classified into the molecular subtypes described for endometrial endometrioid and serous carcinomas. We performed a rigorous histopathological review, immunohistochemical analysis and massively parallel sequencing targeting 300 cancer‐related genes of 32 pure ECCs. Eleven (34%), seven (22%) and six (19%) ECCs showed abnormal expression patterns for p53, ARID1A, and at least one DNA mismatch repair (MMR) protein, respectively. Targeted sequencing data were obtained from 30 of the 32 ECCs included in this study, and these revealed that two ECCs (7%) were ultramutated and harboured mutations affecting the exonuclease domain of POLE . In POLE wild‐type ECCs, TP53 (46%), PIK3CA (36%), PPP2R1A (36%), FBXW7 (25%), ARID1A (21%), PIK3R1 (18%) and SPOP (18%) were the genes most commonly affected by mutations; 18% and 11% harboured CCNE1 and ERBB2 amplifications, respectively, and 11% showed DAXX homozygous deletions. ECCs less frequently harboured mutations affecting CTNNB1 and PTEN but more frequently harboured PPP2R1A and TP53 mutations than non‐POLE endometrioid carcinomas from The Cancer Genome Atlas (TCGA). Compared to endometrial serous carcinomas (TCGA), ECCs less frequently harboured TP53 mutations. When a surrogate model for the molecular‐based TCGA classification was used, all molecular subtypes previously identified in endometrial endometrioid and serous carcinomas were present in the ECCs studied, including POLE, MMR‐deficient, copy‐number high (serous‐like)/p53 abnormal, and copy‐number low (endometrioid)/p53 wild‐type, which were significantly associated with disease‐free survival in univariate analysis. These findings demonstrate that ECCs constitute a histologically and genetically heterogeneous group of tumours with varying outcomes. Furthermore, our data suggest that the classification of ECCs as being generally 'high‐grade' or 'type II' tumours may not be warranted. Copyright © 2017 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.